2019
DOI: 10.1111/mmi.14416
|View full text |Cite
|
Sign up to set email alerts
|

Changes in transcription start sites of Zap1‐regulated genes during zinc deficiency: Implications for HNT1 gene regulation

Abstract: Changes in RNA are often poor predictors of protein accumulation. One factor disrupting this relationship are changes in transcription start sites (TSSs). Therefore, we explored how alterations in TSS affected expression of genes regulated by the Zap1 transcriptional activator of Saccharomyces cerevisiae. Zap1 controls their response to zinc deficiency. Among over 80 known Zap1-regulated genes, several produced long leader transcripts (LLTs) in one zinc status condition and short leader transcripts (SLTs) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 49 publications
(74 reference statements)
0
3
0
Order By: Relevance
“…Therefore, this difference may be caused by different sampling periods of male flowers in the early study. Each promoter deletion fragment has at least one TSS, and the GUS staining results show that different promoter deletion fragments can drive the expression of the GUS gene in Arabidopsis thaliana, indicating that this result may be related to the selected TSS [36,37]. The RcFAH12 promoter deletions could drive GUS gene expression in anthers except for FP1611.…”
Section: Rcfah12 Expression Is Subject To Complex Transcriptional Reg...mentioning
confidence: 94%
“…Therefore, this difference may be caused by different sampling periods of male flowers in the early study. Each promoter deletion fragment has at least one TSS, and the GUS staining results show that different promoter deletion fragments can drive the expression of the GUS gene in Arabidopsis thaliana, indicating that this result may be related to the selected TSS [36,37]. The RcFAH12 promoter deletions could drive GUS gene expression in anthers except for FP1611.…”
Section: Rcfah12 Expression Is Subject To Complex Transcriptional Reg...mentioning
confidence: 94%
“…Case studies have revealed that diverse gene targets are subject to LUTI-based repression, including the genes encoding the kinetochore subunit Ndc80 (J. Chen et al, 2017;Chia et al, 2017), the superoxide dismutase enzyme Sod1 (Vander Wende et al, 2023), the transcription factor Swi4 (Su et al, 2023), and the purine hydrolase enzyme Hnt1 (Van Dalfsen et al, 2018;Tatip et al, 2020). Importantly, the observation that the human protooncogene MDM2 is subject to LUTI-based interference has revealed this form of gene repression is broadly conserved (Hollerer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…When they use the distal TSS/TSSs, there is an overlap with the gene on the other strand of the DNA, however, when they use only proximal TSS/TSSs, the overlap does not occur (Rosikiewicz et al 2021). This dynamically changes under the influence of various intra- and extra-cellular conditions (Makhnovskii et al 2022; Rosikiewicz et al 2021; Tatip et al 2020). It has been described that changes in the TSSs used by certain genes have a translation regulatory function, e.g., in cancers, such as squamous cell carcinomas (Weber et al 2022) and during cerebellar development (P. Zhang et al 2017).…”
Section: Introductionmentioning
confidence: 99%